(untitled) (Sinología hispánica. China Studies Review, 2016)
Based on the research framework of Pragma-Dialectics, the study analyses and evaluates an editorial about Alibaba’s Initial Public Offering (IPO) in The Washington Post to develop a pragma-dialectical approach to critical media discourse analysis. The approach consists of four interrelated parts: reconstruction of argumentation, analysis of strategic maneuvering, evaluation of reasonableness and social criticism on the basis of specific social reality. The research results show that The Washington Post exerts different strategic maneuvering in the whole argumentation process to convince its audience, which mainly reflected in the manipulation of potential topic, audience demand and presentation means. In the case study, strategic maneuvering is specifically supported by the choice of starting points in the opening stage and the design of argumentation structure in the argumentation stage. Owing to the influence from the editorial board’s political stand and self-interest, it doesn’t balance the reasonableness and effectiveness and therefore some manipulations contain fallacious moves. In order to prevent American investors to invest Alibaba’s IPO, when using strategic maneuvering The Washington Post violates freedom rule, standpoint rule and argument scheme rule, especially the application of argumentation scheme for the relation of analogy and argumentation scheme for a causal relation.